The effects of temperatures and volumetric expansion on the diffusion of fluids through solid polymers. Issue 31 (16th April 2017) - Fan, Yiming; Gomez, Antonio; Ferraro, Serena; Pinto, Brian; Muliana, Anastasia; La Saponara, Valeria
ABSTRACT: This study examines moisture sorption behaviors of two glassy polymers, epoxy and vinylester, immersed in different fluids at two temperatures below the glass transition temperatures of the polymers. The main purpose of this study is to understand the effect of volume‐dependent temperatures and deformations on the diffusion process of solid polymers. Diffusivity coefficients are first determined by assuming the diffusion to follow the classical Fickian diffusion. In some cases, moisture sorption led to quite significant changes of volume, and the diffusion process cannot be well described by the Fickian diffusion. In such situation, the coupled deformation–diffusion model for linear elastic isotropic materials presented by Gurtin1 is adopted, as a first approximation. This coupled deformation‐diffusion model reduces to a Fickian diffusion model when the coupling parameters are absent and the volume changes in the solid polymers during diffusion are negligible. A finite difference method is used in order to solve for the coupled deformation‐diffusion model. The model is used to predict the one‐dimensional moisture diffusion in thin plates and the multiaxial three‐dimensional moisture diffusion in dogbone specimens. The multiaxial diffusion in the dogbone specimens is used to validate the calibrated material parameters from the standard thin plate diffusion characterization. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45151. Abstract :